Global and national macroeconometric modelling : a long-run structural approach - Garratt, Anthony (Oxford ; New York : Oxford University Press, 2006)
The book provides a comprehensive description of the state-of-the-art in modelling global and national economies. It introduces the long-run structural approach to modelling that can be readily adopted for use in understanding how economies work, and in generating forecasts for decision-and policy-makers. The book contains a thorough description of recent developments in macroeconomics and econometrics, which should be of interest to advanced students and researchers, but is also written to be accessible and helpful to practitioners in government and the private sector. The transparency and pragmatism of the modelling approach used within this book will be attractive to practitioners who need manageable and interpretable models to answer specific questions.
Introduction -- Macroeconometric modelling : alternative approaches -- National and global structural macroeconometirc modelling -- An economic theory of the long run -- An economic theory of the short run -- Econometric methods : a review -- Probability forecasting : concepts and analysis --The UK macroeconomy -- A long-run structural model of the UK -- Impulse response and trend/cycle properties of the UK model -- Probability event forecasting with the UK model -- Global modelling and other applications -- Concluding remarks.
Includes bibliographical references (p. 343-361) and index.
rpm 20/11/13
Loans
Keywords: Econometric models